Developing graduate profiles through AI-based deep learning training for Social Studies teachers - Neiny Ratmaningsih; Aim Abdulkarim; Diana Noor Anggraini; Pitria Sopianingsih (Universitas Pendidikan Indonesia, 2026)
Teachers often face several challenges in developing instructional materials, which can impact graduate profiles. The objective of this training is to enhance graduate profiles by implementing AI-based deep learning for social studies teachers. The community service program was implemented using an inductive approach in two phases: direct and indirect training, targeting social studies teachers who are members of the Social Studies teachers’ working group (MGMP IPS) in Bandung City, West Java. The training results indicate that AI-based deep learning through chatbots can integrate the principles of mindful, meaningful, and joyful learning, thereby creating a meaningful learning experience. The success of learning depends on teachers’ attention to students’ potential to ensure an efficient learning process, support self-development, and shape character. The training was conducted continuously by encouraging Social Studies teachers to plan, implement, reflect on, and select learning models, methods, and strategies appropriate to students’ characteristics and curriculum requirements. The outcome of this training is the development of graduate profile dimensions encompassing faith, piety, citizenship, critical thinking, creativity, collaboration, independence, health, and communication—all resulting from deep social studies learning oriented toward strengthening national character. Abstrak Sering kali ditemukan guru menghadapi beberapa tantangan dalam menyusun perangkat pembelajaran, sehingga dapat berpengaruh pada profil lulusan. Tujuan pelatihan ini adalah untuk mengembangkan profil lulusan melalui penerapan deep learning berbasis AI bagi guru-guru IPS. Program pengabdian dilaksanakan dengan pendekatan induktif dalam dua tahap, yaitu pelatihan langsung dan tidak langsung, dengan sasaran guru IPS yang tergabung dalam MGMP IPS di Kota Bandung, Jawa Barat. Hasil pelatihan menunjukkan bahwa pembelajaran mendalam berbasis AI melalui chatbot mampu mengintegrasikan prinsip mindful, meaningful, dan joyful learning sehingga menciptakan pengalaman belajar yang bermakna. Keberhasilan pembelajaran bergantung pada perhatian guru terhadap potensi murid agar proses belajar efisien, mendukung pengembangan diri, serta membentuk karakter. Pelatihan dilaksanakan secara berkelanjutan dengan mendorong guru IPS untuk merencanakan, melaksanakan, merefleksikan, dan memilih model, metode, serta strategi pembelajaran yang sesuai dengan karakteristik murid dan tuntutan kurikulum. Hasil akhir dari pelatihan ini mengembangkan dimensi profil lulusan yang mencakup keimanan, ketakwaan, kewargaan, penalaran kritis, kreativitas, kolaborasi, kemandirian, kesehatan, dan komunikasi merupakan hasil dari pembelajaran mendalam IPS yang berorientasi pada penguatan karakter bangsa. Kata Kunci: artificial intelligence; guru IPS; pelatihan; pendekatan pembelajaran mendalam; profil lulusan